Enduring hope and loss: qualitative evidence synthesis of LGBTQ+ experiences of perinatal loss - Darwin, Zoë Josephine; Bainbridge, Ash; Bekiropoulou, Aikaterini; Greenfield, Mari (Frontiers in Psychiatry, 2026)
IntroductionPerinatal healthcare systems, services and research are shaped by cisheteronormative assumptions, i.e. that families involve one woman who carries a pregnancy and one man who is a non-carrying partner; furthermore, assuming that conception has usually resulted from sexual intercourse, with both parties providing gametes. These assumptions obscure and sometimes exacerbate LGBTQ+ people’s experiences and needs. This evidence synthesis aimed to identify and bring together the experiences of LGBTQ+ people who have faced pregnancy or baby loss; collectively perinatal loss.MethodsA qualitative evidence synthesis was conducted using systematic methods. Relevant databases were systematically searched using predefined search terms, and complimented by citation chaining. Eligibility was restricted to empirical qualitative studies published in English, unrestricted by participants’ relationship to the loss (i.e. physically pregnant or not - sometimes respectively described as gestational/birthing or non-gestational/non-birthing parent), type of perinatal loss (e.g. miscarriage, stillbirth), time since loss, setting, publication date, or type of qualitative methodology. Study selection followed a multi-stage screening process. Thematic synthesis was used to analyse and interpret patterns of meaning across included studies.ResultsSeven studies met the eligibility criteria, reported across 10 papers. All seven were conducted in the Global North (including North America, Australia, and Europe). Thematic synthesis generated one overarching theme - enduring hope and loss – which captured the layers of loss experienced by LGBTQ+ people. This included the complexity of loss, and the loss commonly not being felt as an isolated incident, but rather part of a longer process. The three connected themes were: 1. Investment, which included the effort of navigating cisheteronormative systems, frequently after investing time, finances and emotions in assisted conception. 2. Support in relation to loss, highlighting the challenges of accessing support while being marginalised, excluded, or feeling invisible and, at times, unsafe as an LGBTQ+ family. 3. Meaning-making, in the immediate experience of loss, the aftermath of loss and the care received, and the time beyond.ConclusionCisheteronormative systems and interactions have potential to amplify loss and contribute to feelings of disenfranchisement amongst LGBTQ+ people. Further research is needed to evaluate support provided, inclusive of implications for subsequent reproductive choices.